Acute revascularization in ischemic stroke: Updated Swiss guidelines. Issue 1 (30th April 2021) - Michel, Patrik; Diepers, Michael; Mordasini, Pasquale; Schubert, Tilman; Bervini, David; Rouvé, Jean-Daniel; Gasche, Yvan; Schwegler, Guido; Bonvin, Christophe; Nedeltchev, Krassen; Carrera, Emmanuel; Kägi, Georg; et al.
In acute ischemic stroke, intravenous thrombolysis (IVT) and acute endovascular therapy (EVT) have been shown to reduce long-term disability in randomized trials. International guidelines are partially not up to date and may not address situations for which there is limited scientific evidence. The goals of the present guidelines are to summarize the current scientific data for acute revascularization treatments to make sure that all Swiss Centers apply a similar, evidence, or consensus-based treatment standard. A multidisciplinary working group of the Swiss Stroke Society (SSS) searched and reviewed the literature on new randomized controlled trials (RCTs), large case series, meta-analyses, and other guidelines since the previous recommendations in 2009 to elaborate the consensus guidelines. The new RCTs have confirmed the effectiveness of IVT in various populations up to 4.5 h and proven the benefit of acute EVT up to approximately 8 h. For patients with unknown onset (including wake-up stroke), IVT and EVT can be effective up to 24 h after last proof of good health if patients are selected with advanced neuroimaging. Multiple case series and meta-analyses allow narrowing down the indications and relative and absolute contraindications to optimize the benefit–risk ratio of acute revascularization.